EFISIENSI SISTEM BONUS MALUS SEBAGAI MODEL RANTAI MARKOV - Supandi, Supandi (MATEMATIKA, 2006)
. Developed bonus malus system (BMS) is to make the premium paid by insured will be as closed as possible with expected occurrence of claim in every year basis. To study the efficiency of a BMS, we must previously observe the effect of claim frequency on value of premium. The efficiency of Bonus Malus System can be found through its Markov model; that is by found a stationary distribution in form of line vectors of its BMS Markov chain with its components as a function of claim frequency. In this paper, the BMS used is that of Brazil.